Bibliometric Analysis of Language Learning in Elementary Schools: Trends and Future Research Directions - Mowla, Fazlul Anwar; Chowdhury, Shafiqul Alam; Akter, Nusrat Jahan; Bhuiyan, Haque Kabir (Universal Education, 2024)
Language learning in elementary schools is fundamental for children’s literacy and communication development, yet no bibliometric study has comprehensively mapped this field. This study fills that gap by conducting a bibliometric analysis using the Scopus database with the keywords “language learning” AND “elementary school,” yielding 355 documents, of which 204 articles published between 2004 and 2024 were analyzed following PRISMA procedures. Data were processed using Bibliometrix (R) and VOSviewer to examine publication trends, citations, and keyword networks. The results show a significant rise in publications since 2015, driven by global agendas such as SDG 4, the expansion of digital and mobile learning, and national policies emphasizing literacy. Keyword mapping revealed three dominant clusters: language learning and development linked to motivation and anxiety; child development and primary education, highlighting the role of developmental psychology; and language learning disorders, linguistics, and writing, underscoring inclusivity and technical aspects. Recent trends further indicate growing interest in vocabulary acquisition, technology-based pedagogy, and problem-solving approaches. This study offers novelty as the first bibliometric mapping of language learning in elementary schools, providing a holistic overview of research growth, thematic focus, and directions for future inquiry in digital pedagogy, inclusivity, and international collaboration.